PENELITIAN EPIDEMIOLOGI WABAH LEPTOSPIROSIS DI KOTA METROPOLITAN JAKARTA, INDONESIA - Simanjuntak Gindo M; Salma Ma'ruf; Aida Fatmi; Ch, Mashulili; Kurnianto Amien; Feurah Dihan; Siswati Ma'ruf; Wilfried H Purba (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2003)
Jakarta Metropolis was seferely swept by flood in 20 days from January 29 to February 17, 2002. The number of hospitalized patients were increased in many hospitals and Health Centers since the flood occurred. Until the first week of April 2002, it was reported that I 03 cases of leptospirosis were confirmed and 20 persons among these victims died or 19,4% Case Fatality Rate. The highest number ofleptospirosis cases, 35 persons, were occurred in March 10-16, 2002 period while the highest death number, five persons, were occurred in March 3-9, 2002 period. Epidemiology Cross Sectional study was conducted in Central and West Jakarta from where the leptospirosis victims were predominantly reported. All the victims were visited to their addresses. Interview and physical examination were performed to them together with their suspected family members, enviroment surrounding their houses were observed, 2.5 ml serum specimen was collected from each respondent. Rodent trapping was done inside and out side of their houses and animal serum specimens were also collected About 153 human and 142 animal blood sera were collected. Microscopic Agglutination Test was performed for Leptospirosae serovar examination. It was found that 18(11,8%) out of 153human scra were positive of L. pyrogenes serovar pyrogenes 9(5,9% ), L. canicola serovar Canicola 5(3,3% ), L. bataviae serovar Bataviae 4 (2,6%) and L. icterohaemorrhagiaeserovar Icterohaemorrhagiae 4(2,6%) where four persons were infected by two serovars. About 10(9,8%) serum specimens belong to 102 persons up to 40 years old group were positive of leptospirosis antibody serovars, Of 10(8,8%) out 113 human sera which collected from the flooded area up to two weeks period were found positive of Jeptospirosis antibody serovars, All of 153 suspected cases (]00,0%) were suffered from fever, myalgia 107(82,6%), headache 120(78,4%), abdominal pain 90(59,0%), jaundice 68(44,2%) conjunctival suffusion43(28,4%). The species of rodent trapped were Rattus norvegicus 60(42,2%), Rattus rauus.diardii64(45,0% ), Rauus exulans 2(1,4%) and Insectivora'sspecies of Suncus murinus were 16(11,3%). Of 67(47,2%) out 142 animal serum specimens were positive of various Leptospirae serovars, which consisted 39(65,0%) out of 60 R. norvegicus, 20(31,3%) out of 64 R.r. diardii, 2( 100,0%) out of two R. exulans and 6(37,5%) out of 16 S. murinus. Regarding performed serological test, L. bataviae serovar Bataviae was found among 42 animal sera, Liicterohaemorrhagiaeserovar Icterohaemorrhagiae'arnong31 animal sera, L. canicola serovar Canicola among 12 animal sera and L. pyrogenes serovar Pyrogenes among five animal sera. Some serovars were found in some individuals of animal sera